Surrealism in Egypt : Modernism and the Art and Liberty Group - Bardaouil, Sam (I.B. Tauris; Bloomsbury Publishing, 2016)
In the thick of the Second World War, the Cairo-based Surrealist collective Art et Liberte were pioneering new art forms and mounting subversive exhibitions that sent shockwaves across local artistic circles. Born with the publication of their Manifesto Long Live Degenerate Art on December 22nd, 1938, the group rejected the convergence of art and nationalism, aligning themselves with a complex, international and evolving Surrealist movement spanning cities such as Paris, London, Mexico City, New York, Beirut and Tokyo. Art and Liberty created a distinct reworking of Surrealism, which provided a generation of disillusioned Egyptian and non-Egyptian artists and writers, men and women alike, with a platform for cultural reform and anti-Fascist protest. Surrealism in Egypt is the first comprehensive analysis of Art and Liberty's artworks, literature and critical writings on Surrealism. By addressing the group's long-lost and often misconstrued legacy, and drawing on a substantial body of previously unpublished primary documents and more than 200 field interviews, the author charts Art and Liberty's significant contribution towards a new definition of Surrealism.Moving beyond the polarizing dichotomies of Saidian Orientalism, this book rewrites the history of Surrealism itself - advocating for a new definition of the movement that reflects an inclusive vision of art history.
Table of Contents: -- Introduction -- 1. Art and Liberty: A Prehistory -- 2. Fascism at Home: Towards a New Reading of Art and Liberty's Manifesto of December 22, 1938 -- 3. Word to Picture, Picture to Word: The Literary and Pictorial Imagery of Art and Liberty -- 4. Art and Liberty and the Reworking of Surrealism -- 5. Art and Liberty and British Surrealism: Parallels and Overlaps -- 6. From Theory to Practice: The Exhibition as Protest, Art as Rupture -- 7. A Legacy Interrupted: From Art and Liberty to Bread and Liberty -- 8. Post-war Rupture: Art and Liberty and the Beginning of the End -- Conclusion: Art and Liberty Reconsidered Beyond -- Orientalism and the Post-Colonial Lens
Arabic
Keywords: N5300-7418 Visual Arts- History; Surrealism; Egypt